Differences in running biomechanics of elite sprinters, non-elite sprinters and non-runners - Rezvanova, S.; Bobyrev, A.; Skvortsov, D. (ISBS Proceedings Archive (Michigan), 2020)
The aim of the study was to investigate key predictors of fast sprinting. For this purpose, three groups of subjects were evaluated: elite sprinters, non-elite sprinters and non-runners. The analyzed groups consisted of 7, 9 and 11 subjects, respectively. Biomechanical running parameters were collected during the 30-meter acceleration up to maximum speed achievable by the subject. The obtained results revealed clear differences in running biomechanics among the all groups (contact time and step length normalised to body height). Also group results for «step length>body height» and «RSI>1 showed, that the values of these parameters are available only for elite sprinters and non- elite sprinters groups. Date also showed step length normalised to body height to be a highly informative predictor of sprint performance (its correlation coefficient with maximum speed being 0.81).